Malpractice in emergency units [Acil ünitelerde tibbi uygulama hatalari] - (:unkn) unknown (My University, 2008)
Emergency Units are places where emergency personnel provide uninterrupted healthcare. Early diagnosis, immediate intervention and saving lives are the first priority in these places. However, this speedy and complex process sometimes cause issues that may be addressed as "malpractice in healthcare". This article summarizes errors and medical errors seen in the emergency units, analyzes the effects of the emergency working conditions on these errors and suggests preventive measures.